1994
DOI: 10.1007/bf00203145
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio calculations on (OH)4 defects in α-quartz

Abstract: Abstract. Ab initio total energy calculations based on a new optimized oxygen psuedopotential have been used to study the structures and relative energies of e-quartz, a partly (OH)4 substituted version of the e-quartz structure, and interstitial water molecules in e-quartz. Hydrogen bonds formed from two hydroxyl groups of the (OH)4 defects in the substituted e-quartz structure promote a stable structure for the defect e-quartz at low temperature. Comparable ab initio calculation of the energy of the intersti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1
1

Year Published

1995
1995
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 21 publications
0
23
1
1
Order By: Relevance
“…Just as importantly, it permits analytic forces to be computed allowing for relaxation of the ions to their minimum energy configuration. This type of calculation has been used to study defect energies in MgO 18 , OH groups as substitutional defects in quartz 19 , reconstruction of the silicon (111) surface 20 and dissociation of Cl 2 at a silicon surface 21 . One difficulty in using plane-wave pseudopotential methods for oxides has been that the tightly-bound oxygen 2p electrons require a high energy cutoff making the calculations expensive to perform.…”
mentioning
confidence: 99%
“…Just as importantly, it permits analytic forces to be computed allowing for relaxation of the ions to their minimum energy configuration. This type of calculation has been used to study defect energies in MgO 18 , OH groups as substitutional defects in quartz 19 , reconstruction of the silicon (111) surface 20 and dissociation of Cl 2 at a silicon surface 21 . One difficulty in using plane-wave pseudopotential methods for oxides has been that the tightly-bound oxygen 2p electrons require a high energy cutoff making the calculations expensive to perform.…”
mentioning
confidence: 99%
“…The d-component of the Ge pseudopotential is generated in a similar way to match smoothly around the core radius of 1.217 Å to a screened potential that is constructed by carrying out an all-electron calculation on the free Ge atom in the same reference configuration and is chosen to be the local for the KleinmanBylander representation. Although Si and Ge pseudopotential is constructed using only local density approximation (LDA) it has shown to be highly transferable over the required energy ranges from neutral atoms [31], dimers [32], silicon oxide defects [32], and silicon surface reconstruction [33]. For the ultrasoft pseudopotential of H it is generated with an atomic reference electron configuration 1s 1 of core radius r c,s ϭ 0.423 Å, augmentation radius of r aug,s ϭ 0.423 Å for the construction of the pseudized augmentation function, and reference energy of s,1 ϭ Ϫ6.394 eV.…”
Section: Methodsmentioning
confidence: 99%
“…These authors also show that the activation energy for the migration of water molecules in the amorphous structure of SiOs (Hagon et al, 1987) is likely to be more closely related to that for the migration of water molecules in dislocation cores in quartz, a point which is of relevance later. Recent ab initio calculations (Lin et al, 1994) using full periodic boundary conditions rather than a simple cluster configuration indicate that the minimum insertion energy for the water molecule in quartz is 88.15 kJ/mole with respect to well separated water molecules at 0 K.…”
Section: Interstitial Water Moleculesmentioning
confidence: 99%
“…While these may provide a source of water it is not clear that molecular water in this form plays any direct role in the development of the abundant dislocations necessary to the weakening process in quartz. On the basis of electron-optical studies McLaren et al (1983) suggested that small defects in synthetic wet quartz, showing strong electron-optical strain contrast, were bubbles of high pressure fluid which are responsible for the volume increase of the quartz crystal on heating, but this conclusion has recently been seriously challenged (Lin et al, 1994;McConnell et al, 1995), and these defects are now regarded as planar rafts of aggregated [4HIsi defects formed on precipitation. Two aspects of the behaviour of fluid inclusions in quartz are of direct interest in the present discussion.…”
Section: Macroscopic Fluid Inclusionsmentioning
confidence: 99%
See 1 more Smart Citation